A Biology Learning in the Covid-19 Pandemic Period: Pembelajaran Biologi di Masa Pandemi Covid 19 - Ridzal, Dewi Asriani (Universitas Muslim Buton, 2022)
This study aims to analyze the biology learning process during the Covid-19 pandemic. The research method used is a literature review by analyzing 15 articles on biology learning during the Covid-19 pandemic. The results show that online biology learning is less effective and there is also successfully implemented. The implementation of online biology learning requires the use of digital technology-based media, some of the media used include WhatsApp application, Google Meet, Zoom, Campus Management Services (LMS), and virtual labs. The implementation of online learning also faces various obstacles, including limited contingents, networks, and supporting devices such as mobile phones, so evaluations must always be carried out for the learning implementation to take place in the best possible way.